A Comparison Effect of the Imported (Biomin) and Local Iraqi Probiotic on Some Physiological Properties and Intestinal Microflora in Broiler Chicks: Galib. A. AL-Kaissi , Rafid, A. AL-KhalidiI , S.A. Naji - AL-Kaissi, Galib. A. (The Iraqi Journal of Veterinary Medicine, 2006)
The aim of the present study was to compare the effect of two probioticproducts, Biomin and Iraqi Probiotic, on some blood and biochemical propertiesand intestinal microflora population in broiler chicks. A total of 500 Lohmanbroiler chicks, one day old, were randomly distributed into five dietary groups asfollow:T1: chicks fed on diet with half dose of Biomin (1.5 Kg/ Ton diet).T2: chicks fed on diet with full dose of Biomin. (3 Kg/ Ton diet)T3: chicks fed on diet with half dose of Iraqi probiotic. (2.5 Kg/ Ton diet)T4: chicks fed on diet with full dose of Iraqi probiotic. (5 Kg/ Ton diet)T5: chicks fed slandered diet. (Control)Results obtained from the present study showed that both probiotics weresignificantly (ρ > 0.05) increase packed cell volume (PCV), total count ofred blood cells, the concentration of hemoglobin and protein in bloodserum. However, the total count of white blood cells, H/L ratio, and theconcentration of cholesterol in the blood serum were significantly (ρ > 0.05)decreased. Both Probiotics produce a significant decrease in the totalbacterial count, coliform and mold count and increased Lactobacilli countin broiler intestinal contents. Iraqi Probiotic tended to have more comparedeffect in increasing Lactobacilli count in the intestine with both Biominand control groups.